Estates and constitution : the parliament in eighteenth-century Hungary - Szijártó, István M., 1965- (Austrian and Habsburg studies ;, 2020)
"Across eighteenth-century Europe, political power resided overwhelmingly with absolute monarchs, with notable exceptions including the much-studied British Parliament as well as the frequently overlooked Hungarian Diet, which placed serious constraints on royal power and broadened opportunities for political participation. Estates and Constitution provides a rich account of Hungarian politics during this period, restoring the Diet to its rightful place as one of the era's major innovations in government. István M. Szijártó traces the religious, economic, and partisan forces that shaped the Diet, putting its historical significance in international perspective"--